Holocaust victims and perpetrators - Wieland-Burston, Joanne (Journal of analytical psychology, 2012)
The author presents here the results of 12 years of work with a group of psychotherapists in Germany on the subject of the after-effects of the Nazi period on people in psychotherapeutic treatment today. She identifies several typical complexes concerned with issues of identity, loyalty, relationship, authority and aggression. Case examples and references to texts from the Nazi period illustrate the phenomena. The author's concern is that psychotherapists be aware of their own collective (family, ethnic, national) past so that they can fully engage in their work without having to repress painful collective complexes. In training analysis this aspect of the work is especially important so that the following generations of analysts can experience the importance of this level of the collective unconscious.